Winning Factors: How Players' Positional Offensive and Defensive Skills Affect Probability of Victory in the Korea Basketball League. Issue 2 (June 2015) - Choi, Dai-Hyuk; Kim, Su-Mi; Lee, Jang-Won; Suh, Sang-Hoon; So, Wi-Young
This study investigated how the various offensive and defensive skills of Korea Basketball League (KBL) players in different court positions affected the outcome of basketball games. The records of 540 games played by 10 KBL teams over a five-month period were analyzed. In a multiple logistic regression, six offensive and six defensive factors served as independent variables, while the victory or defeat for each game served as the dependent variable. Centers contributed positively to victory with higher assists on offense and higher blocked shots on defense. Forwards positively contributed to victory on offense with a higher two-point shot percentage, free throw shot percentage, and number of assists, as well as a lower number of turnovers. Forwards also positively contributed to victory on defense with more defensive rebounds and fewer fouls with free throws. Guards positively contributed to victory with higher two-point and three-point shot percentages, more assists, and fewer turnovers on offense, as well as more defensive rebounds, more steals, and fewer fouls with free throws on defense. This study found that the particular offensive and defensive skills of KBL players in different positions affected whether or not games ended in victory.